A mock terrorism application of the P300-based concealed information test - Meixner, John B.; Rosenfeld, J. Peter (Psychophysiology, 2011)
Previous studies examining the P300‐based concealed information test typically tested for mock crime or autobiographical details, but no studies have used this test in a counterterrorism scenario. Subjects in the present study covertly planned a mock terrorist attack on a major city. They were then given three separate blocks of concealed information testing, examining for knowledge of the location, method, and date of the planned terrorist attack, using the Complex Trial Protocol (Rosenfeld et al., 2008). With prior knowledge of the probe items, we detected 12/12 guilty subjects as having knowledge of the planned terrorist attack with no false positives among 12 innocent subjects. Additionally, we were able to identify 10/12 subjects and among them 20/30 crime‐related details with no false positives using restricted a priori knowledge of the crime details, suggesting that the protocol could potentially identify future terrorist activity.